Cossacks in Jamaica, Ukraine at the antipodes : essays in honor of Marko Pavlyshyn - Pavlyshyn, Marko; Achilli, Alessandro; Yekelchyk, Serhy; Yesypenko, Dmytro (Ukrainian studies (Boston, Mass.), 2020)
"This bilingual collection of essays celebrates Marko Pavlyshyn's outstanding contribution to the study of modern and contemporary Ukrainian literature and culture. With its many methodological approaches and the variety of periods, authors and texts that it analyzes, the book reflects and builds on Pavlyshyn's willingness to modernize our understanding of Ukrainian literature as an instrument of communication between authors, readers and the nation from the late eighteenth century to the present day. Hopefully these essays will inspire readers and scholars to continue their journey through Ukrainian culture, in a context profoundly marked by the role of literary texts as agents of nation building and social evolution"--